Teacher travel claim system - Jong, Mei Sze (Universiti Malaysia Sarawak, UNIMAS, 2006)
The usage of the computer is in sync with our daily life. Most of the application we met today is not longer manually. Most the routines can be done using technology such computer. Therefore, the Teacher Travel Claim System (TTCS) is developed to help the teachers in SK Niup on claim making. The implementation of TTCS is based on user’s requirements. The system’s goal is enable user to fill their claim easily. By the features provided in the system, the users can gain benefit by making the claim much easier.